Gramineous fraction of the invasive flora of the Caucasus - S. A. Litvinskaya; R. T. Abdyeva (Юг России: экология, развитие)
Aim. Questions about the invasive flora of the Caucasus regions are a most important issue under discussion. The aim of the research is to identify the species composition of the family Poaceae, which are alien to the Western Caucasus, and their distribution over the floristic regions of the Caucasus.Material and Methods. Material: Disturbed communities. Methods: analysis of herbarium collections, route reconnaissance studies of the territory of the Western and Eastern Caucasus, detailed geobotanical route studies with photography, population mapping and analysis of literary sources.Results. 96 invasive cereal species in the territory of the Western Caucasus and the Ciscaucasia were identified and their current geographical distribution shown. 5 levels of danger have been established in terms of the amount of invasive cereal flora in the floristic regions of the Caucasus. An ecological analysis is given for 96 species of cereals in the Caucasus.Conclusion. 96 invasive cereal species were identified and their current geographical distribution in the territory of the Western Caucasus and the Ciscaucasia shown. 5 levels of danger have been established in terms of the amount of such invasive flora in the Caucasus’ floristic regions. An ecological analysis is given for these 96 invasive species of cereals.